RETRACTED: Effects of tocilizumab and dexamethasone on proinflammatory cytokines and antioxidants in acute kidney injury caused by oleic acid-induced ARDS - Erol, Huseyin Serkan; Demirci, Beste; Alhilal, Mohammad; Terzi, Funda (Research Square Platform LLC, 2023)
Abstract The authors have requested that this preprint be removed from Research Square.
Keywords: 3. Good health